ANTIMICROBIAL ACTION OF PSIDIUM GUAJAVA L. EXTRACT AGAINST ENTEROCOCCUS FAECALIS AND CANDIDA ALBICANS STRAINS: A PILOT STUDY - Baldoni, Giovana de Abreu; Meccatti , Vanessa Marques; de Carvalho, Lara Steffany; Carvalho , Cláudio Antonio Talge; Oliveira, Luciane Dias de; Hasna, Amjad Abu (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Endodontic treatment consists of decontamination of the root canal using irrigants like Sodium Hypochlorite (NaOCl). However, some microorganisms resist conventional therapies, causing relapse and secondary infections. Substances with microbicidal power and potential to become new irrigants need to be studied. Thus, the objective of the present study was to evaluate the antimicrobial potential of Psidium guajava L. (guava tree) extract against clinical and standard (ATCC) strains of Enterococcus faecalis and Candida albicans. For this purpose, the extract was produced from the raw material (leaves and shoots) diluted in the hydroethanolic vehicle (EtOH: H2O / 50:50) for subsequent microbiological analysis. The Minimum Inhibitory Concentration (MIC) and Minimum Microbicidal Concentration (MMC) of the plant extract were tested, according to the Clinical and laboratory standards institute (CLSI) guidelines, on four strains: E. faecalis (ATCC and clinic) and C. albicans (ATCC and clinic). The extract of P. guajava did not produce antifungal action on C. albicans, however, it showed microbicidal potential against strains of E. faecalis, showing MIC of 0.20%. This concentration was lower than the MIC of NaOCl which was 0.31%, a solution that is commonly used in dental clinics. In conclusion, the hydroethanolic extract of P. guajava presents bactericidal action against E. faecalis, being a natural product with potential for future studies regarding the development of new endodontic irrigants.